2021
DOI: 10.18494/sam.2021.3322
|View full text |Cite
|
Sign up to set email alerts
|

Optical, TSL, and OSL Properties of Copper-doped Cesium Bromide Transparent Ceramics Prepared by SPS

Abstract: The optical, thermally stimulated luminescence (TSL), and optically stimulated luminescence (OSL) properties of CsBr:Cu transparent ceramics were evaluated. As the photoluminescence properties, two emissions around 460 and 490 nm related to Cu + and Cu 2+ ions, respectively, were observed under excitation at around 300 nm, and the quantum yield of CsBr:Cu (0.01%) was 17.3%. After X-ray irradiation, all the samples showed a broad TSL and OSL emission band around 400-500 nm. All the samples exhibited good propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In addition, while personal dose monitoring applications require an effective atomic number (Z eff ) close to that of the human body in terms of bioequivalence (Z eff = 7.29), based on the composition of C 5 H 40 O 18 N, (4) IP applications such as dental diagnostics require a large Z eff for high detection efficiency. Various material forms such as single crystals, (5)(6)(7) ceramics, (8)(9)(10)(11)(12)(13) and glasses (14,15) have been investigated for dosimeter applications, and glasses have industrial advantages such as a low production cost and high moldability in comparison with single crystals and ceramics. (16) However, only Ag-doped phosphate glasses have been commercially applied in practical use, (17,18) and there have been only a few reports on the TSL and OSL properties of glasses with a large Z eff .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while personal dose monitoring applications require an effective atomic number (Z eff ) close to that of the human body in terms of bioequivalence (Z eff = 7.29), based on the composition of C 5 H 40 O 18 N, (4) IP applications such as dental diagnostics require a large Z eff for high detection efficiency. Various material forms such as single crystals, (5)(6)(7) ceramics, (8)(9)(10)(11)(12)(13) and glasses (14,15) have been investigated for dosimeter applications, and glasses have industrial advantages such as a low production cost and high moldability in comparison with single crystals and ceramics. (16) However, only Ag-doped phosphate glasses have been commercially applied in practical use, (17,18) and there have been only a few reports on the TSL and OSL properties of glasses with a large Z eff .…”
Section: Introductionmentioning
confidence: 99%
“…Prior research revealed that typical Cu-doped phosphors have two decay time constants of microsecond order due to the 3d 9 4s 1 -3d 10 transition of Cu + ions. (23)(24)(25)(26) In our measurements, such values were obtained for the PL decay curves monitored at 490 nm. Thus, we assigned the origin of the 490 nm peak to the 3d 9 4s 1 -3d 10 transition of Cu + ions.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we focused on a translucent ceramic, (22)(23)(24) a new material form of scintillators that can be used to enhance lattice-defect luminescence. Translucent ceramics have more lattice defects than other material forms such as single crystals, (25,26) which are generally used as scintillators; thus, ZnO translucent ceramics may have enhanced LY.…”
Section: Introductionmentioning
confidence: 99%